In-air fluence profiles and water depth dose for uncollimated electron beams - Toutaoui, Abdelkader; Aichouche, AmarNassim; Adjidir, Kenza; Chami, AhmedChafik (Journal of medical physics, 2008)
Advanced electron beam dose calculation models for radiation treatment planning systems require the input of a phase space beam model to configure a clinical electron beam in a computer. This beam model is a distribution in position, energy, and direction of electrons and photons in a plane in front of the patient. The phase space beam model can be determined by Monte Carlo simulation of the treatment head or from a limited set of measurements. In the latter case, parameters of the electron phase space beam model are obtained by fitting measured to calculated dosimetric data. In the present work, data for air fluence profiles and water depth doses have been presented for electron beams without an applicator for a medical linear accelerator. These data are used to parameterize the electron phase space beam model to a Monte Carlo dose calculation module available in the first commercial (MDS Nordion, now Nucletron) Monte Carlo treatment planning for electron beams.